2019
DOI: 10.1016/j.contraception.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Counseling and referrals for women with unplanned pregnancies at publicly funded family planning organizations in Texas

Abstract: Objectives: To compare pregnancy options counseling and referral practices at state- and Title X-funded family planning organizations in Texas after enforcement of a policy restricting abortion referrals for providers participating in state-funded programs, which differed from Title X guidelines to provide referrals for services upon request. Study design: Between November 2014 and February 2015, we conducted in-depth interviews with administrators at publicly funded family planning organizations in Texas ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Our results showed that women who visit their physician for routine checkups have a lower probability of unwanted pregnancy. Similarly, previous ndings have shown that providing women with birth control techniques and counseling reduces unplanned pregnancies and abortions (84)(85)(86). A prospective study of 10,000 reproductive-aged women found that structured counseling could improve knowledge and consistent use of contraceptive methods, which lowers the rate of unintended pregnancy, abortion, and births (87).…”
Section: Discussionmentioning
confidence: 85%
“…Our results showed that women who visit their physician for routine checkups have a lower probability of unwanted pregnancy. Similarly, previous ndings have shown that providing women with birth control techniques and counseling reduces unplanned pregnancies and abortions (84)(85)(86). A prospective study of 10,000 reproductive-aged women found that structured counseling could improve knowledge and consistent use of contraceptive methods, which lowers the rate of unintended pregnancy, abortion, and births (87).…”
Section: Discussionmentioning
confidence: 85%
“…A study participant in Canada explained how their doctor refused to provide care or refer to another facility because it was against the doctor’s beliefs [ 43 ]. Others participants in the United States were unable to get referrals from their doctors to receive abortion services in the hospital, which would have been covered by Medicare (the federal government health coverage program), because of the doctor’s personal beliefs [ 45 ]. Even in cases where providers do not hold personal views against abortion, perceptions of abortion opposition in the community can lead facility staff to withhold information about available services to women [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Others participants in the United States were unable to get referrals from their doctors to receive abortion services in the hospital, which would have been covered by Medicare (the federal government health coverage program), because of the doctor’s personal beliefs [ 45 ]. Even in cases where providers do not hold personal views against abortion, perceptions of abortion opposition in the community can lead facility staff to withhold information about available services to women [ 45 ]. These findings point to the importance of continuing to investigate how refusals to provide abortion care are defined by providers and communicated to their patients [ 44 ], and to determine the overall economic impact on women and their decisions around care.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Title X, a federal grant program funding sexual and reproductive health care, stopped requiring grantees to provide pregnancy options counseling and prohibited clinicians from providing abortion referrals, even at the patient's request 13 . Individual states may also prohibit state‐funded organizations from providing abortion referrals 14 …”
Section: Introductionmentioning
confidence: 99%